(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Organophosphate (op) poisoning is a common poisoning in India with suicidal and accidental ingestion. It is associated with high morbidity and mortality. We present 23 year old male with history of OP poisoning who developed intermediate syndrome with polyneuropathy. Patient managed conservatively along with multidisciplinary team approach leading to a successful management.